Dukungan Sosial Guru Dalam Upaya Membimbing Kemandirian Anak Moderate Intellectual Disability - Aulia Kirana; Agustini Agustini (Fakultas Psikologi Universitas Tarumanagara, 2018)
In the world of education, some children significantly have below-average intelligence andthrow obstacles in ourselves in their development. Children known as moderate intellectualdisability, IQ range from 40-54, mayors have appeared in daily activities, such as selfdevelopmentactivities and need the training to foster independence. Teachers must be able toassist, such as serving needs, awards, funds, and providing advice to help children withintellectual disability. Teachers provide social assistance as an effort to guide self-reliance tofoster a sense of responsibility. Also, teachers can develop teaching material models, such asthematic and individual learning tailored to the ability to learn and learn, make decisions.This research is qualitative research, with 4 teachers as the respondent. The results of thisstudy indicate that teachers who educate children with moderate intellectual disability whohave proposed several people, including, emotional, and instrumental in guiding studentindependence. The results of the study on four teachers who educate children with moderateintellectual disability, indicate that teachers who have proposed several support, including,emotional, and instrumental in an effort to guide student independence. The samplingtechnique in this study used the sampling criteria through sampling using subjects that werein accordance with the research criteria. Furthermore, suggestions, guidance, suggestionsfor guidance in learning can be provided by parents and students or media in the form ofdrawings, and supporting tools for teaching and learning activities and suggestions to helpdevelop students with parents.